1975
DOI: 10.1677/joe.0.0660407
|View full text |Cite
|
Sign up to set email alerts
|

The SYNERGISTIC ACTION OF Α-Melanocyte-Stimulating HORMONE AND TESTOSTERONE ON THE SEBACEOUS, PROSTATE, PREPUTIAL, HARDERIAN AND LACHRYMAL GLANDS, SEMINAL VESICLES AND BROWN ADIPOSE TISSUE IN THE HYPOPHYSECTOMIZED-CASTRATED RAT

Abstract: Alpha-Melanocyte-stimulating hormone was shown to act synergistically with testosterone to stimulate the sebaceous, prostate and the seminal vesicles in hypophys-ectomized-castrated rats. The sebaceous glands differed from the other three organs in that alpha-MSH not only acted synergistically, but also had a significant effect which was independent of the presence of exogenous testosterone. The response of the brown adipose tissue to testerone, considerably reduced by hypophysectomy, was not restored by alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 12 publications
5
18
0
Order By: Relevance
“…These observations were confirmed in other investigations (14,(19)(20)(21)23). In the present study,'LNCaP cells did not respond to TGF-B, and this observation is in agreement with earlier publications.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These observations were confirmed in other investigations (14,(19)(20)(21)23). In the present study,'LNCaP cells did not respond to TGF-B, and this observation is in agreement with earlier publications.…”
Section: Discussionsupporting
confidence: 94%
“…In a previous study, exogenous PDGF stimulated the proliferation of PC-3 cells in a dose-dependent manner and overcame dexamethasone's inhibition of PC-3 cell growth (19). The treatment of LNCaP cells with PDGF did not stimulate their growth (20).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Previous reports have shown that acute a-MSH injection releases into the urine of male rats and mice a pheromonal signal that elicits attacks from opponents even when swabbed onto the fur of nonaggressive stimulus mice (Nowell and Wouters, 1975;Nowell et al, 1980). Although the male rodent preputial gland contributes to the aggression-eliciting pheromonal signal, preputial pheromones are not the sole source of this signal (Ingersoll et al, 1986;Jones and Nowell, 1973;Novotny et al, 1985), and the activity of this exocrine gland depends on pituitary and gonadal hormones, such as alpha-MSH and testosterone, respectively Ebling et al, 1975).…”
Section: Introductionmentioning
confidence: 99%